1999
DOI: 10.1046/j.1570-7458.1999.00525.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism in the olfactory orientation of adult Cydia pomonella in response to α‐farnesene

Abstract: The role of host plant‐derived volatile substances on the behaviour of adult codling moth, Cydia pomonella L. (Lepidoptera: Tortricidae) is poorly understood. We tested the response of females and males to a range of α‐farnesene dosages. Natural α‐farnesene from apples contains the E,E and Z,E isomers in varying proportions. No difference in the response of C. pomonella to preparations containing two different proportions of the E,E and Z,E isomers was noted (77:20.7 or 1.2:84.7% E,E and Z,E isomers respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(90 citation statements)
references
References 21 publications
(34 reference statements)
1
89
0
Order By: Relevance
“…33 (E,E)-α-Farnesene, the main constituent of apple odor, stimulates oviposition and attracts neonate larvae and adult females of Cydia pomonella at short range. 34 This compound is also found in many other plants. Linalool acted electrophysiologically on C. pomonella female antennae.…”
Section: Resultsmentioning
confidence: 87%
“…33 (E,E)-α-Farnesene, the main constituent of apple odor, stimulates oviposition and attracts neonate larvae and adult females of Cydia pomonella at short range. 34 This compound is also found in many other plants. Linalool acted electrophysiologically on C. pomonella female antennae.…”
Section: Resultsmentioning
confidence: 87%
“…The majority of these PNs arborised in the anterior central part of the AL. α-farnesene has been shown to be a potent attractant in the codling moth, Cydia pomonella, another tortricid moth (Sutherland and Hutchins, 1972;Hern and Dorn, 1999;Bengtsson et al, 2001;Coracini et al, 2004). Our previous study showed that AL neurons in both males and females of L. botrana responded to α-farnesene (Masante-Roca et al, 2002).…”
Section: Discussionmentioning
confidence: 97%
“…In contrast to males, the sesquiterpenes (E,E)-a-farnesene and (E)-bfarnesene elicited strong responses in female AL neurons (Tables1, 2). (E,E)-a-farnesene, a main component of apple headspace , is detected by very sensitive ORNs (Bäckman et al, 2000) and has been shown to contribute to the attraction of females (Hern and Dorn, 1999) and males, in combination with (E)-b-farnesene .…”
Section: Integration Of Behaviourally Relevant Chemical Cuesmentioning
confidence: 99%